Arthur Spiderwick's field guide to the fantastical world around you - DiTerlizzi, Tony.; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2005)
Presents a full-color illustrated field guide that describes the fourteen creatures featured in the Spiderwick Chronicles, as well as fifteen additional creatures.
Includes bibliographical references (p. 120-121).
School Library Journal, March 2006.
Publisher's Weekly, October 2005.
Booklist, February 2006.
Horn Book, April 2006.
8.9
Keywords: Fairies -- Fiction; Brothers and sisters -- Fiction; Single-parent families -- Fiction; Siblings -- Fiction; Fantasy fiction